The Development of Advance Organizer Based Distance Learning in Chemistry Bonding Material - Widyastuti, Niken; Riswandi, Riswandi; Fitriawan, Helmy (Journal of Education Technology, 2021)
The spread of the Covid-19 virus requires the government to take a policy of organizing education online. Learning chemical bonding material is strived to be developed according to the needs of students and learning objectives that are reflected in the curriculum. This study aims to develop advance organizer-based distance learning on chemical bonding material and measure the effectiveness of this product. This study uses the Dick and Carey development model approach. The instruments used included assessment questionnaires, observations, interviews, validation sheets and tests of students' cognitive knowledge. The data obtained were analysed using quantitative descriptive statistics and data on the effectiveness of learning using an n-gain score. The results of this study obtained online learning products with an average validation score of 3.51 on a scale of 4.00 and the student gain value before and after using advance organizer-based online learning was 0.52. The conclusion of this research is that advance organizer-based online learning products on chemical bonding material are very feasible and effective. These findings will be an input for efforts to develop chemical bonding materials and research the development of chemistry learning during a pandemic.